Crosstalk between obesity and MMP-9 in cardiac remodelling –a cross-sectional study in apparent treatment-resistant hypertension. (4th March 2017) - Ritter, Alessandra Mileni Versuti; de Faria, Ana Paula; Barbaro, Natália; Sabbatini, Andréa Rodrigues; Corrêa, Nathália Batista; Brunelli, Veridiana; Amorim, Rivadavio; Modolo, Rodrigo; Moreno, Heitor
Abstract: The balance between matrix metalloproteinases (MMP) and their tissue inhibitors (TIMP) plays a key role in the development of hypertension and obesity. We aimed to evaluate the levels of MMP-2 and 9 and TIMP-2 and -1 in obese and non-obese apparent treatment-resistant hypertensive subjects (aTRH) and its association with cardiac hypertrophy. This cross-sectional study enrolled 122 subjects and divided into obese aTRH ( n  = 67) and non-obese ( n  = 55) group. Clinical and biochemical data were compared between both groups, including office BP, ambulatory BP, plasma MMP-2 and 9, TIMP-2 and 1 and left ventricular mass index (LVMI). We found higher MMP-9 levels and MMP-9/TIMP-1 ratio in obese aTRH subjects but no difference in MMP-2 and TIMP-1 levels. Obesity influenced MMP-9 levels [β = 20.8 SE =8.6, p  = 0.02) independently of potential confounders. In addition, we found a positive correlation between MMP-9 and anthropomorphic parameters. Finally, obese aTRH subjects with left ventricular hypertrophy (LVH) had greater MMP-9 levels compared with non-obese with LVH. Our study suggests that MMP-9 levels are influenced by obesity and may directly participate in the progressive LV remodelling process, suggesting a possible role for a higher cardiovascular risk in apparent resistant hypertensive subjects.